Дерева як множини рівня псевдогармонічних функцій на площині - Полулях, Є.О. (Український математичний журнал, 2013)
Предложено достаточное условие для того, чтобы образ вложения ψ: T \V₀ → R²
, где T — дерево, конечное или бесконечное, V₀ — множество его вершин валентности 1, был множеством уровня псевдогармонической функции. Let T be a finite or infinite tree and let V₀ be the set of all vertices of T of valency 1. We propose a sufficient condition for the image of the imbedding ψ: T \V₀ → R² to be a level set of a pseudoharmonic function.